Catalogue of scaling laws and similitude questions in geotechnical centrifuge modelling. Issue 3 (September 2007) - Garnier, J.; Gaudin, C.; Springman, S.M.; Culligan, P.J.; Goodings, D.; Konig, D.; Kutter, B.; Phillips, R.; Randolph, M.F.; Thorel, L.
Abstract : Some forty years ago, when geotechnical centrifuge modelling had been rediscovered and was being developed once more after the early work of Phillips (1869), only a few studies were devoted to the questions and concerns about scaling laws and similitude conditions. During the first decades, it was relatively easy for researchers to keep themselves informed about the main outcomes of these studies and to take them into account when designing new centrifuge model tests. This is obviously not true today following the welcome growth in terms of the large number of centrifuge facilities now in operation around the world. It is increasingly difficult, but yet absolutely essential, to know about the relevant developments concerning studies into the scaling laws and, furthermore, into the limits of the domains of the use of centrifuge modelling. On the other hand, new media offers a significant opportunity to provide this resource to the physical modelling community. New topics are investigated by many researchers as they become more inventive in the ways in which geotechnical centrifuge modelling is applied to solve pressing problems within geotechnical engineering, and across other disciplines too. Innovative work presenting comparisons between centrifuge model tests and true scale tests are providing original data on the validity of the scaling factors. During the TC2 meeting at St John's (Canada) in July 2002, the first author, J. Garnier (LCPC), suggested making an inventory of the scaling laws and similitude questions relating to centrifuge modelling. The aim of this catalogue is to present the questions already solved (with inclusion of the references of the papers where the results have been presented) and the unsolved problems (on which research should continue). The first draft of this catalogue is now available and it is hoped that it will become a useful tool for scientists and researchers involved in centrifuge modelling. Of course, this catalogue will be regularly updated, every four years during the International Conferences on Physical Modelling in Geotechnics. The latest version of the catalogue is available on the TC2 website (www.tc2.civil.uwa.edu.au ).